Analisa Faktor-Faktor Dining Experience dalam Menciptakan Minat Beli Ulang di Café “Kantin” Kota Palembang - Andhika Chandra Lesmana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
The phenomenon of establishing coffee shops in Indonesia has become a trend in recent years. This can be seen from the significant increase in the number of coffee shops and domestic coffee consumption in recent years. Palembang is one of the cities in Indonesia, especially southern Sumatra, which cannot be separated from the growth of coffee shops or often known as cafes. Of course, the role of experience felt by consumers is a separate assessment for a cafe which will later become a differentiator in every place, especially cafes which are expected to provide a positive experience for people to come and buy the product again. This research aims to analyze more deeply the Dining Experience Factors in Creating Repurchase Interest in the